Urotensin II receptor on preoperative biopsy is associated with upstaging and upgrading in prostate cancer. (November 2015) - De Cobelli, Ottavio; Buonerba, Carlo; Terracciano, Daniela; Bottero, Danilo; Lucarelli, Giuseppe; Bove, Pierluigi; Altieri, Vincenzo; Coman, Ioman; Perdonà, Sisto; Facchini, Gaetano; Berretta, Massimiliano; Di Lorenzo, Giuseppe; et al.
Aim: A higher Gleason score was associated with a lower tumor urotensin II receptor (UTII-R) expression in prostate cancer patients.Methods: A retrospective review of formalin-fixed paraffin-embedded tumor tissue derived from those who had prostatectomy and matching biopsy specimens was conducted at six Institutions. UTII-R expression was evaluated on biopsy by immunohistochemistry.Results: A total of 58 subjects undergoing radical prostatectomy were included. At multivariate analysis, low UTII-R expression was a significant predictor of Gleason upgrading, with an odds ratio of 10.3 (95% CI: 1.55–68.4), and of pathology upstaging, with an odds ratio of 11.1 (95% CI: 1.23–100.48).Conclusions: UTII-R expression on biopsy was associated with Gleason upgrading and pathology upstaging in prostate cancer patients.